2016
DOI: 10.4103/amhsr.amhsr_33_16
|View full text |Cite
|
Sign up to set email alerts
|

Cervical necrotizing fasciitis: A potentially fatal disease with varied etiology

Abstract: Necrotizing fasciitis was recognized centuries ago by physicians. It is a rapidly progressive and potentially fatal soft-tissue infection that is typified by soft-tissue necrosis, especially affecting the subcutaneous tissues and fascia. Cervico-facial necrotizing fasciitis is said to be uncommon, but when it occurs, it is often of odontogenic origin and has severe consequences if not promptly treated. Possible underlying systemic diseases and the source of infection should be addressed and treated appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Necrotizing fasciitis is an aggressive soft tissue infection that can be polymicrobial or due to a single organism [ 1 , 2 , 11 , 64 ]. Multiple organisms as well as mixed infections have been reported to cause necrotizing fasciitis of odontogenic origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrotizing fasciitis is an aggressive soft tissue infection that can be polymicrobial or due to a single organism [ 1 , 2 , 11 , 64 ]. Multiple organisms as well as mixed infections have been reported to cause necrotizing fasciitis of odontogenic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic necrotizing fasciitis is often characterized by rapidly progressive bacterial infection along multiple fascial tissue planes, leading to vascular compromise, thrombosis, or rupture, along with necrosis of adipose, integumentary, muscular, and subcutaneous and cutaneous tissues. Preexisting immunosuppressive conditions such as diabetes mellitus may predispose patients to odontogenic necrotizing fasciitis, and may increase the mortality risk [ 1 , 2 , 11 , 64 ]. In the present study approximately 20% of patients were reported to have DM, and these patients were 9 times more likely to die from their odontogenic necrotizing fasciitis than non-diabetic patients ( p = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent instrumentation, odontogenic infection, and penetrating injury are also important risk factors that have been implicated [ 2 , 5 ]. Though the most common sites affected by NF are the lower extremities, abdomen, and the perineum [ 4 ], involvement of other sites such as the head and neck, upper extremities, and thorax have been described [ 6 , 7 ]. The most common microbes that have been isolated are Streptococcus pyogenes , Staphylococcus aureus , and Clostridium perfringens [ 1 ], although Escherichia coli , Pseudomonas spp., Bacteroides spp., Klebsiella pneumoniae , and Streptococcus agalactiae have also been reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing fasciitis (NF) is an uncommon progressive infection of the fascia and the subcutaneous tissues with high mortality and morbidity rate. The term “necrotizing fasciitis” was first mentioned by Wilson (1952) to emphasize that fascial necrosis was the key feature in the progression of the disease and in the majority of his own cases a beta-hemolytic Staphylococcus was the most common pathogen isolated [1]. Subsequent studies with sophisticated methods of bacteriological investigations have shown the majority of cases to be due to mixed pathogens [2].…”
Section: Introductionmentioning
confidence: 99%